Old wires and new waves : - Harlow, Alvin Fay (Appleton-Century company, incorporated, 1936)
This book to the early history of the telegraph, as against the remarkable technical develop ments of the past quarter or half century. May it be suggested that the birth and infancy of ideas are intrinsically more note worthy, more important, than their middle age The centuries of groping for a method of quick communication, the one long century of mans striving to make electricity his servant, the pioneer days of the telegraph, when not only it but all America was simple and crude these are to most folk to-day so exotic, the last-named phase is to the student so significant a picture of the youth of American society and the nation, that, in the judgment of the author, they should be dealt with in detail for the benefit of a generation which knows them not. On the other hand, the rapid developments in telegraph, tele phone, and wireless in recent days are described at length in newspapers and magazines as they appear and they come so swiftly and we are so inured to them that the astounding inven tion of yesterday has to-day become a commonplace, and to morrow is superseded by something still more miraculous.